The Profile of Type 1 Leprosy Reaction at Leprosy Division of Dermatology and Venerology Outpatient Clinic of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia - Brigita Ika Rosdiana; Linda Astari; Astindari Astindari; Iskandar Zulkarnain; Damayanti Damayanti; Budi Utomo; M. Yulianto Listiawan (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Leprosy is a chronic infectious disease caused by Mycobacterium leprae. Type 1 leprosy reaction is a delayed hypersensitivity reaction caused by the increased response of cellular-mediated immunity to the Mycobacterium leprae antigen on the skin and nerves with a reversal result. The clinical manifestation includes inflammation which can cause skin and nerve lesions, swell, to permanent disabilities. Purpose: To describe the demographic and clinical profile of type 1 leprosy reaction at the Leprosy Division of the Dermatology and Venerology Outpatient Clinic of Dr. Soetomo General Academic Hospital in 2017–2019. Methods: This was a descriptive study. We used secondary data from the medical records of leprosy patients at the Leprosy Division of Dermatology and Venereology outpatient clinic, Dr. Soetomo General Academic Hospital Surabaya, from January 2017 to December 2019. Result: Out of 364 patients, 65 (17.9%) had type 1 reactions. They were mostly in productive age at 35–55 years old (56.9%). The patients were predominantly male (75.4%), with normal nutritional status (98.5%) and negative bacterial index (72.3%). The most common types of leprosy were BB (Borderline) with 61.6% and BL (Borderline Lepromatous) with 20.8%. All patients took WHO (World Health Organization) MDT (Multi Drug Therapy) MB (Multi-Bacillary). Conclusion: The profile of type 1 leprosy reaction at the Leprosy Division of Dermatology and Venerology Outpatient Clinic of Dr. Soetomo General Academic Hospital in 2017–2019 shows an average data as follows: age 35–55 years, male, normal nutritional status, negative bacterial index, leprosy type BB.